Winners and losers in U.S. marine aquaculture under climate change - C R Fong; J DeCesaro; G Clawson; M Frazier; B S Halpern; H E Froehlich (Environmental Research Letters)
Mariculture will be important to meeting global seafood food demand in the coming decades. Yet, the threat of climate change—such as rising ocean temperatures—on mariculture performance remains uncertain. This is particularly true at small spatial scales relevant to most producers. Additionally, mariculture is often limited by regulations that impose restrictions on production, creating potential hurdles for anticipating and adapting to climate change. We focus on mariculture performance in the United States (U.S.), where state and federal policies and exposure to climate change vary substantially and likely interact. We map a current and future mariculture performance index by combining the first high resolution downscaled (0.083°) climate outputs for U.S. waters, species-specific physiological requirements, and policy restrictions. We find high current performance that will increase under warming oceans, with spatial variation that will amplify existing regional differences. Generally, performance will increase in the north and decrease in the south. While the permitting process is not intentionally climate-forward, permitted species outperformed taxon averages, yet state policies often limit production of seaweeds and finfishes, which perform well. Thus, we sit at a critical juncture where the U.S. could capitalize on its seemingly favorable environmental conditions through re-alignment of regulations to support portfolio diversification to include climate-resilient species.